When Fear of Missing Out Meets Fatigue: Understanding How Social Media Dynamics Shape Travel Intentions in West Sumatra - Astri Yuza Sari; Ofanto Ofanto; Hari Setia Putra; Fitria Ridhaningsih; Jefriyanto Jefriyanto (Master of Management, School of Business and Management, Petra Christian University, 2025)
In today’s digital landscape, the Fear of Missing Out (FoMO) has become a strong psychological driver influencing how people choose travel destinations, particularly when those places gain popularity on social media. However, the constant stream of curated posts can also trigger social media fatigue (SMF), reducing enthusiasm for travel. This study investigates how FoMO affects tourists’ intentions to visit destinations in West Sumatra and explores whether SMF mediates this relationship. Data were collected through an online questionnaire distributed via Instagram and WhatsApp among users who regularly engage with travel-related content. A total of 500 valid responses were analyzed using SmartPLS to test both direct and mediating effects. The findings highlight how digital and psychological factors jointly shape travel behavior and offer destination marketers insights into creating authentic, sustainable social media strategies that balance online excitement with emotional well-being.